Identify the training needs during the service for psychological counselors in secondary schools in Benghazi - Alhasi, Enas Almabrouk (Journal of Educational and Psychological Sciences, 2020)
The present study aims to identify the training needs during the service for psychological counselors in secondary schools in Benghazi and to know the differences in the training needs of psychological counselors, according to the variable of gender, scientific qualification and years of service. The study population consisted of (63 counselors), the who provide psychological counseling in secondary schools in Benghazi to identify their training needs. In order to achieve the objective of the study a questionnaire tool was constructed. Results of the study counselors are in great need of training and that there are statistically significant differences in the training needs, according to gender. qualification and service years.